Effects of hydrothermal carbonization process parameters on phase composition and the microstructure of corn stalk hydrochars - Zhang Zhenghao; Shen Xin; Zhang Yingyi; Zhang Guangqiang; Xie Zhaohui; Han Zhichen (High Temperature Materials and Processes)
The steel metallurgy industry is a high energy consuming and high polluting industry. In order to reduce the consumption of fossil fuels such as coke and coal powder and environmental pollution, it is urgent to develop a new type of clean energy for green metallurgy. Biomass straw energy, as a renewable and clean energy source, has attracted widespread attention from metallurgical researchers. In this work, the corn stalk hydrochars were prepared by hydrothermal carbonization (HTC) method at different carbonization temperatures, carbonization times, and mass ratios, aiming to provide a green and sustainable energy source for the metallurgical industry. In addition, the influences of parameter changes on phase composition, microstructure, and calorific value were also analyzed. Results manifested that the elevation of temperature and time promoted the HTC process, contrary to the solid–liquid proportion. It was worth noting that short carbonization time and high mass ratios were unconducive to the dissolution of harmful phase KCl, which affected the application of hydrochar. Under the optimal carbon process conditions (T = 260°C, t = 40 min, S/L = 2%), the corn stalk hydrochar has a smaller particle size (<50 μm), higher calorific value (22.34 MJ·kg−1), and carbon content (76.46 wt%), which has a great potential to replace anthracite and promote the sustainable development of the metallurgical industry.